Prospective randomized controlled trial evaluating cap-assisted colonoscopy vs standard colonoscopy - Tee, Hoi-Poh (The WJG Press and Baishideng, 2010)
AIM: To study the significance of cap-fitted colonoscopy in improving cecal intubation time and polyp detection rate. METHODS: This study was a prospective randomized controlled trial conducted from March 2008 to February 2009 in a tertiary referral hospital at Sydney. The primary end point was cecal intubation time and the secondary endpoint was polyp detection rate. Consecutive cases of total colonoscopy over a 1-year period were recruited. Randomization into either standard colonoscopy (SC) or cap-assisted colonoscopy (CAC) was performed after consent was obtained. For cases randomized to CAC, one of the three sizes of cap was used: D-201-15004 (with a diameter of 15.3 mm), D-201-14304 (14.6 mm) and D-201-12704 (13.0 mm). All of these caps were produced by Olympus Medical Systems, Japan. Independent predictors for faster cecal time and better polyp detection rate were also determined from this study. RESULTS: There were 200 cases in each group. There was no significant difference in terms of demographic characteristics between the two groups. CAC, when compared to the SC group, had no significant difference in terms of cecal intubation rate (96.0% vs 97.0%, P = 0.40) and time (9.94 ± 7.05 min vs 10.34 ± 6.82 min, P = 0.21), or polyp detection rate (32.8% vs 31.3%, P = 0.75). On the subgroup analysis, there was no significant difference in terms of cecal intubation time by trainees (88.1% vs 84.8%, P = 0.40), ileal intubation rate (82.5% vs 79.0%, P = 0.38) or total colonoscopy time (23.24 ± 13.95 min vs 22.56 ± 9.94 min, P = 0.88). On multivariate analysis, the independent determinants of faster cecal time were consultant-performed procedures (P < 0.001), male patients (P < 0.001), non-usage of hyoscine (P < 0.001) and better bowel preparation (P = 0.01). The determinants of better polyp detection rate were older age (P < 0.001), no history of previous abdominal surgery (P = 0.04), patients not having esophagogastroduodenoscopy in the same setting (P = 0.003), trainee-performed procedures (P = 0.01), usage of hyoscine (P = 0.01) and procedures performed for polyp follow-up (P = 0.01). The limitations of the study were that it was a single-center experience, no blinding was possible, and there were a large number of endoscopists. CONCLUSION: CAC did not significantly different from SC in term of cecal intubation time and polyp detection rate.